HP GARAGE: USM EE STUDENT PROJECTS EXHIBITED AT HP MALAYSIA MANUFACTURING - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
On 16 March 2017, HP Malaysia Sdn. Bhd. has extended their invitation to the School of Electrical and Electronics Engineering (School EE), Universiti Sains Malaysia (USM) to exhibit student projects at their newly officiated HP Garage.